Association between bortezomib dose intensity and overall survival in mantle cell lymphoma patients on frontline VR-CAP in the phase 3 LYM-3002 study*. Issue 1 (2nd January 2019) - Robak, Tadeusz; Huang, Huiqiang; Jin, Jie; Zhu, Jun; Liu, Ting; Samoilova, Olga; Pylypenko, Halyna; Verhoef, Gregor; Siritanaratkul, Noppadol; Osmanov, Evgenii; Pereira, Juliana; Mayer, Jiri; et al.
Abstract: The pivotal LYM-3002 study compared frontline rituximab plus cyclophosphamide, doxorubicin, vincristine and prednisone (R-CHOP) with bortezomib, rituximab, cyclophosphamide, doxorubicin and prednisone (VR-CAP) in newly diagnosed mantle cell lymphoma (MCL) patients for whom stem cell transplantation was not an option. This post hoc subanalysis of the VR-CAP data from LYM-3002 evaluated the effect of bortezomib dose intensity on OS in patients who completed ≥6 cycles of treatment. From the end of cycle 6, patients receiving ≥4.6 mg/m 2 /cycle of bortezomib had significantly longer OS (but not PFS) compared with those receiving <4.6 mg/m 2 /cycle by univariate analysis (HR 0.43 [95% CI: 0.23–0.80]; p = .0059). This association remained significant in multivariate analysis adjusting for baseline patient and disease characteristics (HR 0.40 [95% CI: 0.20–0.79]; p = .008]. Higher bortezomib dose intensity was the strongest predictor of OS in newly diagnosed MCL patients receiving VR-CAP. Clinicaltrials.gov identifier: NCT00722137.